Membincang Kembali Poligami: Telaah Kesejarahan atas Praktek Poligami Dalam Islam - Agus Purnomo (Faculty of Sharia UIN Kiai Ageng Muhammad Besari Ponorogo, 2006)
This study aims to examine the practice of polygamy in Islam from a historical perspective, by exploring the social, cultural, and legal background surrounding it. Polygamy in Islam is often a subject of debate, especially in relation to the interpretation of verses from the Qur'an and their historical context. This study uses a qualitative method with a literature study approach, examining classical and contemporary sources on the law and practice of polygamy in various periods of Islamic history. The results show that polygamy in Islam has a flexible legal basis, with certain conditions that emphasize fairness. In a historical context, the practice of polygamy is influenced by social factors and the needs of the times, not merely as a general norm. This study emphasizes that the understanding of polygamy must consider the historical context and the purpose of sharia, so that its application remains relevant to the principle of justice in Islam.